TECHNOLOGY OF USING BALANCED SCORECARDS OF THE TEACHER'S LEVEL OF PREPAREDNESS - Axmatjonov Xasanbek Valijon ugli; Abdilakimov Gofur Abdixalikovich (Journals Park Publishing, 2025)
The growing demand for measurable educational quality has prompted institutions to adopt data-driven methods to evaluate and enhance teacher preparedness. One such method is the Balanced Scorecard (BSC), traditionally used in business, now adapted to education as a strategic tool for assessing and developing professional competencies. This article explores the technology of applying balanced scorecards to determine and improve the preparedness levels of teachers across pedagogical, methodological, digital, and psychological domains. It presents a systematic framework for implementation, discusses indicator selection, and outlines monitoring mechanisms that align teaching performance with institutional goals. The use of BSC not only ensures transparency and accountability but also fosters continuous professional development.
Keywords: Balanced Scorecard, teacher preparedness, competency assessment, educational quality, performance metrics, strategic planning, professional development.